Hubungan Kecerdasan Verbal dan Kecerdasan Logika Matematika dengan Kemampuan Menyelesaikan Soal Cerita Matematika Siswa SD - Muncarno Muncarno (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This research is motivated by the low ability of grade V students of SD Negeri 8 Metro Timur in solving the math story problem. The purpose of this study is to determine the significance or not the relationship between linguistic intelligence and logical-mathematical intelligence with the ability to solve the mathematics story problem of grade V students of SD Negeri 8 Metro Timur. This type of research is a correlational ex-postfacto study. Data collected by the testing techniques. The data collection instrument is a matter of multiple choice test and analysis test that has been checked for its validity and reliability. Hypothesis test results showed that there is no significant relationship between linguistic intelligence and logical-mathematical intelligence with the ability to solve the mathematics story problem of grade V students of SD Negeri 8 Metro Timur. This is caused by the existence of other factors that can affect the level of ability to solve math story problems, the intervention of variables, and the lack of maximum measuring tools prepared by researchers.